PENGARUH UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PT ANEKA TAMBANG (ANTAM), TBK PERIODE 2012-2024 - Deri Darmawan; Yulian Bayu Ganar (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to determine the effect of company size (measured by the natural logarithm of total assets) and capital structure (measured by the Debt to Equity Ratio/DER) on profitability (measured by Return on Assets/ROA) at PT Aneka Tambang (ANTAM), Tbk for the period 2012-2024. This research method uses a descriptive quantitative approach. The type of sample used is secondary data from the company's financial statements processed using multiple linear regression through SPSS 27, with the classical assumption test showing normal data, no multicollinearity, heteroscedasticity, or autocorrelation. The results show that company size has no significant effect partially (t-count 0.214 < t-table 2.228, sig 0.835 > 0.05), while capital structure has a significant negative effect (t-count -3.267 < t-table 2.228, sig 0.008 < 0.05). Simultaneously, company size and capital structure significantly influence profitability, with a significance value of 0.004 < 0.05, with an F-test of 10.056 > F-table of 4.10. The R² coefficient of determination test results show 66.8% of the variance in profitability, while the remaining 33.2% is influenced by factors outside the research model.